(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Moringa oleifera (MO) has been recognized for its numerous beneficial properties. This study aimed to evaluate the potential antihypertensive effects of MO seeds in rats subjected to Nω-nitro-L-arginine methyl ester (L-NAME) exposure. Fifty male Wistar rats were randomly divided into five groups of 10 rats each for the experiment. Group A served as the control, received normal saline only, Group B received L-NAME (40 mg/kg) only, Group C received L-NAME (40 mg/kg) + 10% MO feed, Group D received L-NAME (40 mg/kg) + 20% MO feed, and Group E received L-NAME (40 mg/kg) + Lisinopril (10 mg/kg). Treatment was daily and covered a period of 5 weeks. Blood pressure and electrocardiographic measurements were obtained using a non-invasive tail cuff blood pressure device and a 6/7 lead computer ECG equipment, respectively. Heart and kidney tissues were analyzed for oxidative stress parameters, and immunohistochemistry and histopathology of the heart and kidney were conducted using standard methods. L-NAME treatment led to a significant increase in diastolic and systolic values compared to the control group. Serum nitric oxide concentration significantly decreased in rats that received L-NAME alone, while co-treatment with MO and Lisinopril showed a significant increase in nitric oxide levels. Co-treatment with MO and Lisinopril significantly reduced malondialdehyde (MDA) concentrations in the cardiac and renal tissues, whereas L-NAME alone caused a significant increase in MDA concentration. The expressions of cardiac and renal caspase-3 significantly increased in L-NAME alone treated rats, while co-treatments with MO and Lisinopril significantly reduced the expressions of caspase-3. In conclusion, co-treatment with MO effectively reduced arterial pressure and indices of hypertension in rats, mitigated the oxidative stress and apoptosis induced by L-NAME. Therefore, the inclusion of MO seeds in hypertension management may serve as an effective remedy.